A holistic perspective of sales research: areas of consideration to develop more comprehensive conceptual and empirical frameworks. Issue 4 (1st October 2020) - Rapp, Adam; Gabler, Colin; Ogilvie, Jessica
Abstract: Research investigating relationships and phenomena within the professional selling discipline has been on-going for the past 100 years. Within that timeframe, there have been countless conceptual and empirical frameworks presented, tested, and published. Importantly, there has been a tendency toward parsimonious research for easier understanding and presentation. While this parsimony makes interpretation and testing more straight forward, there are many factors within the selling context which, when considered, could fundamentally shift relationships. This article reviews some of the most relevant factors, including: data sample concerns, measurement problems, boundary conditions, temporal aspects, multilevel perspectives, and actors/agents involved. Using systems theory as a guiding lens, we present a summary of each factor and consider how they may influence conceptual, empirical, and theoretical frameworks within the sales discipline.